CELSIUS: an international project providing integrated, systematic, cost-effective large-scale IoT solutions for improving energy efficiency of medium- and large-sized buildings - Ma Z.; Santos A.Q.; Shaker H.R.; Yussof S.; Eriksen P.M.; Hornum J.; Jrgensen B.N. (Springer Nature, 2023)
Buildings; Climate change; Cost effectiveness; Gateways (computer networks); Integrated control; Internet of things; Life cycle; Middleware; Building energy performance; Cloud platforms; Cost effective; Indoor climate; Integrated systems; International projects; IoT network; Large-scales; Large-sized; System solution; Energy efficiency